Defining the optimal template of salvage lymph node dissection for unilateral pelvic nodal recurrence of prostate cancer following radical prostatectomy. (28th October 2022) - Van Eecke, Henri; Devos, Gaëtan; Vansevenant, Bram; Vander Stichele, Arthur; Devlies, Wout; Berghen, Charlien; Everaerts, Wouter; De Meerleer, Gert; Joniau, Steven
Abstract : Objectives: Several retrospective studies have shown that salvage bilateral pelvic lymph node dissection (sLND) is a valid treatment option in the setting of oligorecurrent nodal prostate cancer following radical prostatectomy. Little is known about the optimal template of such sLND in patients with strictly unilateral pelvic recurrence on PET‐CT imaging. In this study, we investigated whether a unilateral pelvic sLND could be sufficient in such a setting. Methods: We retrospectively collected data of patients treated with sLND between 2010 and 2019 at the University Hospitals, Leuven. Patients were included if they developed recurrence following radical prostatectomy, characterized by ≤3 unilateral pelvic lymph node metastases on Choline or PSMA PET‐CT and received a super‐extended bilateral pelvic sLND as first metastasis‐directed therapy. As a primary endpoint, we investigated in how many cases a unilateral sLND would have been sufficient. Results: In total, 44 patients with strictly unilateral pelvic recurrence were treated with super‐extended bilateral pelvic sLND. In 5 out of 44 (11%) patients, histological examination showed presence of prostate cancer in the contralateral hemi‐pelvis. In the group with a single positive node on imaging prior to sLND, only 1 out of 27 (3%) patients had contralateral disease at final pathology. No one (0%) in this group subsequently developed recurrence in the contralateral hemi‐pelvis following sLND. Conclusions: In conclusion, this study suggests that unilateral pelvic sLND could be sufficient in patients with a single unilateral pelvic lymph node recurrence on PET/CT imaging.